Differing Roles of the Face and Voice in Early Human Communication: Roots of Language in Multimodal Expression - Jhang, Yuna; Franklin, Beau; Ramsdell-Hudock, Heather L.; Oller, D. Kimbrough (Frontiers in Communication, 2017)
Seeking roots of language, we probed infant facial expressions and vocalizations. Both have roles in language, but the voice plays an especially flexible role, expressing a variety of functions and affect conditions with the same vocal categories—a word can be produced with many different affective flavors. This requirement of language is seen in very early infant vocalizations. We examined the extent to which affect is transmitted by early vocal categories termed “protophones” (squeals, vowel-like sounds, and growls) and by their co-occurring facial expressions, and similarly the extent to which vocal type is transmitted by the voice and co-occurring facial expressions. Our coder agreement data suggests infant affect during protophones was most reliably transmitted by the face (judged in video-only), while vocal type was transmitted most reliably by the voice (judged in audio-only). Voice alone transmitted negative affect more reliably than neutral or positive affect, suggesting infant protophones may be used especially to call for attention when the infant is in distress. By contrast, the face alone provided no significant information about protophone categories. Indeed coders in video-only could scarcely recognize the difference between silence and voice when coding protophones in video-only. The results suggest that partial decoupling of communicative roles for face and voice occurs even in the first months of life. Affect in infancy appears to be transmitted in a way that audio and video aspects are flexibly interwoven, as in mature language.